2020
DOI: 10.1111/gtc.12792
|View full text |Cite
|
Sign up to set email alerts
|

m6A demethylase ALKBH5 promotes proliferation of esophageal squamous cell carcinoma associated with poor prognosis

Abstract: Esophageal squamous cell carcinoma (ESCC) is one of the most fatal types of malignant tumors worldwide. Epitranscriptome, such as N6‐methyladenosine (m6A) of mRNA, is an abundant post‐transcriptional mRNA modification and has been recently implicated to play roles in several cancers, whereas the significance of m6A modifications is virtually unknown in ESCC. Analysis of tissue microarray of the tumors in 177 ESCC patients showed that higher expression of m6A demethylase ALKBH5 correlated with poor prognosis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 35 publications
4
51
0
Order By: Relevance
“…Among the 5 genes, ALKBH5 was the only protective gene for the prognosis of EAC. Nonetheless, a previous study investigated the association between ALKBH5 and prognosis in 177 patients with ESCC, and identi ed ALKBH5 as the rst demethylase that accelerated cell cycle progression and promoted cell proliferation of ESCC cells, suggesting that the up-regulation of ALKBH5 was associated with poor prognosis in ESCC [35]. Conversely, ALKBH5 has been reported to inhibit pancreatic cancer motility by demethylating lncRNA KCNK15-AS1 [43], which agrees with the result in our study to some extent.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Among the 5 genes, ALKBH5 was the only protective gene for the prognosis of EAC. Nonetheless, a previous study investigated the association between ALKBH5 and prognosis in 177 patients with ESCC, and identi ed ALKBH5 as the rst demethylase that accelerated cell cycle progression and promoted cell proliferation of ESCC cells, suggesting that the up-regulation of ALKBH5 was associated with poor prognosis in ESCC [35]. Conversely, ALKBH5 has been reported to inhibit pancreatic cancer motility by demethylating lncRNA KCNK15-AS1 [43], which agrees with the result in our study to some extent.…”
Section: Discussionsupporting
confidence: 91%
“…Esophageal cancer is one of the most aggressive malignant tumors with two main histological subtypes, EAC and ESCC. Several studies have explored the association between m 6 A modi cations and ESCC [28,34,35];…”
Section: Discussionmentioning
confidence: 99%
“…Effectors including RBM15, ALKBH5, and YTHDF2 can regulate the cell cycle biological process. 34 36 Another study similarly reported that YTHDF2 mediated the degradation of RNAs containing m 6 A in mammals. 37 However, the involvement of m 6 A in DNA mismatch repair has not previously been reported; this relationship is a potential avenue for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Functional analysis showed that ALKBH5 could inhibit the proliferation, migration and invasion of EC cells. However, a recent study found that ALKBH5 promotes the proliferation and migration of ESCC [ 27 ]. These results contradict previous findings.…”
Section: The Role and Significance Of M 6 A Methylation In Esccmentioning
confidence: 99%